112 Urinary tract infections in paediatric renal transplant recipients. (22nd November 2019) - Abdulsamea, Sameh; Bryant, William; Margetts, Ben; Booth, John; Marks, Stephen
Abstract : Introduction: Renal transplantation remains the best modality of renal replacement therapy in children with end stage kidney disease, the majority of whom have congenital anomalies of the kidneys and urinary tract (CAKUT). Febrile urinary tract infections (UTI) can cause acute kidney injury (AKI) and worsen chronic kidney disease (CKD). After renal transplantation, episodes of UTI can adversely affect renal allograft survival by causing interstitial scarring and injury, although there is a paucity of data in the literature. Management of UTI in paediatric renal transplant recipients (pRTR) is more complex compared to other healthy children. There are no current guidelines or evidence for management of this common problem. Patients and methods: This was a retrospective review of pRTR at GOSH between 2010 and 2018. Data were collected from the hospital computer based systems with digital research environment and analysed using Analyxagility programme. pRTR were divided into three major groups: (a) No UTI group; (b) Infrequent UTI group (less than one UTI episode per year) and (c) Frequent UTI group (one or more UTI per year). Results: 243 pRTR aged 1.3 to 17.9 (median 10.3) years), of whom 60.8% were males with 47% with primary diagnosis of CAKUT. There was a significant decline in estimated glomerular filtration rate (eGFR) in the group with UTI compared to those without UTI. In addition to the frequency of UTI in those with CAKUT, we found that the original pathology contributed to the decline in renal function (eg. recurrent FSGS). Conclusion: Frequent UTI can adversely affect renal allograft function and requires prompt and effective treatment to reduce AKI and CKD. Guidelines needs to be developed to manage UTI in order to protect renal allograft function and survival (figure 1 ).